The political system and parliamentary life in Iran for the years 1979-1996 - Akar, Wisam Hadi (Al-Adab Journal, 2021)
Adopted the political system in Iran after the Islamic revolution in 1979, the work of the four major powers which constitute the political system. The first of these authorities (religious leader), while other authorities are (legislative, executive and judicial). The legislative branch consists of the Islamic Republic of Iran is a system of two organizations: (Islamic Consultative Assembly), and (the Guardian Council) .osiktsr discussed to highlight the role of the (Islamic Consultative Assembly), because it represents Barlman.oma (the Guardian Council), the aim is to ensure matching the legislation passed by the Islamic Consultative Assembly with Islamic rules and the Constitution. The research focused on the Iranian political system and the parliamentary system between (1979-1996), and it was divided into four themes basis. The first of which touched on a brief overview of the Iranian political system after the 1979 Islamic revolution. He studied the second axis legislative power, specifically the powers (of the Islamic Shura Council). While eating the third axis the most important political parties and movements in Iran and its role in the political system and parliamentary life of Iran, especially (the Islamic Republican Party), and the last axis has Odzna it works election cycles since 1980 and until 1996, and focused strictly on the last session because it produced the arrival (reformist), who had a role in supporting their candidate for the presidency of Mohammad Khatami and two consecutive terms.